Cr (III), Fe (III), Co (II) and Cu(II)Metal ions complexes with azo compound derived from 2-hydroxy quinolin synthesis, characterization, thermal study and antioxidant activity - Abdulrazzaq, Adhraa Ghazi; Al-Hamdani, Abbas Ali Salih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Azo-ligand-(HL)([4-((2-hydroxyquinolin-3-yl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide] ) ,  (2- hydroxy quinolin  derivative),reacts with the next metal ions (Cr (III), Fe (III),Co (II) and Cu(II))  forming stable complexes with unique geometries such as(tetrahedral for bothCo (II) and  Cu (II), octahedral for both Cr (III) and Fe (III)). The creation of such complexes was detected by employing spectroscopic means involving ultraviolet-visible which proved the obtained geometries, Fourier transfer proved the involvement of coordinated water molecule in all complexes besides the pyrolysis (TGA & DSC) studies proved the coordination of water residues with metal ions inside the coordination sphere as well as chlorine atoms. Moreover element-micro-analysis and AAS that gave corresponding outcome with theoretically counting outcome.  Magnetic quantification scan also indicates the unique geometries of complexes. The degradation of reactive oxygen entities for the compounds were estimated toward (DPPH-radical then matched to the standard-natural antioxidant, Gallic acid. The incomes display good radical degradations-activities.The lower IC50 value, the higher antioxidant activity. Depending on this conception, the order of our compounds besides Azo-species-HL is as follows: (G_A [Cr(L)(H2O)Cl]> [Fe(L)(H2O)2Cl2]> [Cu(L)(H2O)Cl]).